Some Characteristics of Islamic Journalism Based on Al Quran - M. Yoserizal Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Prophet Muhammad SAW as a role model has been made and gives examples of how the application of journalism itself. Prophet does his message through writing, that is, when he sends a letter to the kings or heads of tribes in Madinah in order to invite to the road of Islam. A journalist should be able to convince mad'u let that propaganda purposes can take place  without any problem. Journalistic as a method in a very strategic propaganda .Beside it can be enjoyed by many people, the product of journalism also can be more lasting or durable, because it can be stored or read anytime. Journalism propagation of Islam is actually not a new method of propaganda, because the Prophet has implemented a method of propaganda  by sending a letter of propaganda to the kings who do not know and embrace Islam.